2013
DOI: 10.1038/nn.3599
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a unique TGF-β–dependent molecular and functional signature in microglia

Abstract: Microglia are myeloid cells of the central nervous system (CNS) that participate both in normal CNS function and disease. We investigated the molecular signature of microglia and identified 239 genes and 8 microRNAs that were uniquely or highly expressed in microglia vs. myeloid and other immune cells. Out of 239 genes, 106 were enriched in microglia as compared to astrocytes, oligodendrocytes and neurons. This microglia signature was not observed in microglial lines or in monocytes recruited to the CNS and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

120
2,498
10
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,143 publications
(2,711 citation statements)
references
References 60 publications
120
2,498
10
5
Order By: Relevance
“…We confirmed that all cells in our platform shared the same gene expression characteristics of microglia ( Table 1). As a control measure for cell purity, our data confirmed the presence of TGF-μ1 in each sample, as previously reported (Butovsky et al, 2014).…”
Section: General Overview Of the Whole Transcriptome Sequencingsupporting
confidence: 90%
“…We confirmed that all cells in our platform shared the same gene expression characteristics of microglia ( Table 1). As a control measure for cell purity, our data confirmed the presence of TGF-μ1 in each sample, as previously reported (Butovsky et al, 2014).…”
Section: General Overview Of the Whole Transcriptome Sequencingsupporting
confidence: 90%
“…Collectively, these results provide compelling evidence that the phenotypic characteristics of the brain's myeloid component are altered substantially after SE, wherein myeloid cells that infiltrate the brain express high levels of Ly6C, a canonical marker of peripherally derived monocytes (37,38). Moreover, the appearance of Ly6C high CD11b + myeloid cells after SE is reliant on CCR2.…”
Section: Se (mentioning
confidence: 79%
“…The TGF signaling pathway has long been considered to play a key role in the regulation of inflammation and microglia activation 38, 39. It has also been shown to be a key regulator of C1q expression and synaptic pruning in the developing visual system 40.…”
Section: Discussionmentioning
confidence: 99%